2016
DOI: 10.6000/2292-2598.2016.04.01.7
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Integration of Causal Coherence in People with Down Syndrome: Evidence from Figurative Comprehension

Abstract: Contextual integration is seldom explored in people with Down syndrome (DS). This study aimed to investigate this ability by comparing causal inferences made by people with DS who were presented with homonyms embedded within sentences and asked to choose which of three interpretations (figurative meaning, literal meaning, or unrelated meaning) was correct. Accuracy was the dependent variable. Each homonym was presented in a scenario familiar to the participants. The results revealed that the participants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Further evidence of problematic semantic processing of words in people with DS compared to the control group was observed, indicating the atypical development of semantic networks in people with DS by conceptual integration from semantic relatedness. Similar to Hsu (2016Hsu ( , 2019, the findings in our study showed that people with DS were deviant in semantic processing using the false memory paradigm.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Further evidence of problematic semantic processing of words in people with DS compared to the control group was observed, indicating the atypical development of semantic networks in people with DS by conceptual integration from semantic relatedness. Similar to Hsu (2016Hsu ( , 2019, the findings in our study showed that people with DS were deviant in semantic processing using the false memory paradigm.…”
Section: Discussionsupporting
confidence: 84%
“…People with DS showed the lowest accuracy in integrating ambiguities into preceding contexts, suggesting less capability in selecting the correct interpretation of ambiguities. In grouping semantic related concepts, people with DS showed deviancy in priming picture backgrounds (e.g., a sports store) and picture objects (e.g., a pair of snickers vs. a pair of high heels; Hsu, 2016). While people with Williams syndrome (WS) and the mental-age (MA) controls primed only the semantic-related pairs, people with DS primed both semantic-related and -unrelated pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on people with Down Syndrome (DS) by Hsu [29], using the same stimuli and procedures, revealed that people with DS were deviant in causal inferences compared to healthy controls. The results indicated that distinct genotypes contributed to different phenotypes in people with neurodevelopmental disorders [30].…”
Section: Introductionmentioning
confidence: 94%
“…Deviant semantic knowledge in processing ambiguous words in contexts was observed in people with DS [ 6 ]. People with DS showed the lowest accuracy in integrating ambiguities into preceding contexts, suggesting less capability in selecting the correct interpretation of ambiguities.…”
Section: Introductionmentioning
confidence: 99%